Persahabatan dalam Perspektif Platonis: Sebuah Refleksi bagi Pemuda Kristiani - Tanto, Wignyo; Sabdono, Erastus; Daniel, Albertus; Takain, William; Erastus, Stephanie (JURNAL TERUNA BHAKTI, 2024)
Young people who exist and interpret their relationships horizontally really need to understand the meaning of their relationships, of course, in their friendships. The fundamental problem is that young people prioritize reciprocity in their friendly relations rather than the value of "kindness." In Plato's view, friendship can be likened to a triangle, where the level of interchange between actors is relative, not primary. To find out vague problems, researchers used the Gap Method and a literature study approach. This discussion results in young Christians interpreting their existence in relationships as free of horizontal relationships alone. Still, instead, they pursue the vertical relationship of "God" together. Christian youth who involve God in their friendship relationships will go beyond epithumia and thumos relationships; their relationships will be at the logistic level. Abstrak Pemuda yang bereksistensi dan memaknai relasinya secara horizontal, sangat perlu memahami makna dari relasinya, tentu dalam persahabatannya. Permasalahan mendasarnya adalah pemuda lebih memprioritaskan resiprositas di dalam relasi persahabatannya, ketimbang nilai “Kebaikan”. Persahabatan dalam pandangan Platon dapat diibaratkan sebagai suatu segitiga “triangular”, di mana tingkat resiprositas antar pelaku memiliki sifat yang relatif, bukan yang utama. Untuk mengetahui permasalah yang samar-samar, peneliti menggunakan Metode Gap dan pendekatan studi kepustakaan. Hasil dari pembahasan ini, pemuda Kristen yang memaknai eksistensinya dalam berelasi, ia tidak terbelenggu dalam relasi horizontal semata, melainkan mereka bersama-sama mengejar relasi vertikal “Tuhan”. Pemuda Kristen yang melibatkan Tuhan di dalam relasi persahabatannya akan melampaui relasi epithumia dan thumos, relasi mereka akan berada pada level logistikon.